INTERVENSI KEPERAWATAN KECEMASAN PADA PASIEN PRE OPERASI: LITERATUR REVIEW - Chatarina Hatri Istiarini; Efriane Pali Osa; Maria Titin Inya Ede (Universitas Respati Yogyakarta, 2021)
Nursing Interventions for Anxiety in Patients Preoperative: Literature ReviewBackground: one of the psychological effects of surgery is anxiety (Sutejo, 2018). Anxiety management can be done in pharmacology (doctors) or non-pharmacology (nurses). One of the preoperative anxiety nursing interventions was learned through the identification of various related studies / Integrated Literature Review (IRL). Thus the authors are interested in identifying